Return to Play and Functional Outcomes Following Treatment of Acute Achilles Tendon Ruptures: A Systematic Review and Meta-Analysis - Dexter Seow MB BCh, MRCSI; Braydon Bak MB BCh; Yu Ze Evan Teo MBBS, MMed, FRCS; Muhammed Yaser Hasan MBBS (AKU), MCI (NUS), MMed (Ortho), FRCSEd (Ortho); Christopher J. Pearce MB ChB, MFSEM (UK), FRCS (TrOrth) (Foot & Ankle Orthopaedics)
Category: Ankle Introduction/Purpose: Acute Achilles tendon rupture (AATR) is a common injury. Return to play (RTP) and functional outcomes are critical to treatment success for acute Achilles tendon rupture (AATR). This systematic review and meta-analysis explored treatment superiority essential in optimal treatment selection concerning individual patients and their expectations regarding RTP and functional outcomes. Methods: A systematic review was conducted with specific search terms. Potentially relevant studies were identified via a search of the PubMed ® and Embase databases by two authors. This study was in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The inclusion criteria were: randomized controlled trials that reported RTP rates and/or continuous functional outcome scores following the treatment of AATR, full-text studies published in a peer-review journal, published year ≥ 1990, and written in English. The exclusion criteria were: animal studies, in vitro studies, non-randomized clinical studies, and reviews. The included studies were assessed regarding the level and quality of evidence. Fixed-effects models were employed for I2 < 25% and random-effects models for I2 ≥ 25%. Results: The literature search included 46 studies. The LoE of all studies was per eligibility criteria. The mean QoE (modified Jadad Scale) was 5.7. The RTP rate meta-analysis of surgical versus conservative treatment revealed no significant difference. This was similar to the subgroup analysis of open repair and conservative treatment. The RTP rate and Achilles Tendon Total Rupture Score (ATRS) meta-analysis of open repair + earlier rehabilitation (ER) versus + later rehabilitation (LR) also revealed no significant differences. The mean time to RTP meta-analysis of open repair + ER versus + LR showed that open repair + ER was significantly favored (-4.19 weeks; P = 0.002). The ATRS meta-analysis of conservative treatment with ER versus with LR revealed no significant difference. Conclusion: This meta-analysis has revealed that the RTP rates following treatment of AATR are high. The decision for surgical versus conservative treatment or open repair + ER versus + LR for AATR should not be selected based on the expectation of RTP. However, open repair + ER can be advocated over + LR for reduced mean time to RTP.